Pore-scale characterization of tight sandstone in Yanchang Formation Ordos Basin China using micro-CT and SEM imaging from nm- to cm-scale. (1st December 2017) - Liu, Xuefeng; Wang, Jianfu; Ge, Lin; Hu, Falong; Li, Chaoliu; Li, Xia; Yu, Jun; Xu, Hongjun; Lu, Shuangfang; Xue, Qingzhong
Abstract: In this work, we measured the porosity, permeability, electrical resistivity and NMR T2 spectrum of the tight sandstone samples from Yanchang Formation Ordos Basin China. The experimental results indicate weak correlation between porosity and other bulk properties. A workflow of multi-scale digital rock technique is proposed to characterize pore geometry and connectivity in order to understand the ability of fluid flow or electric conduct of tight sandstones. A series of SEM images tiles (MAPS technique) with a resolution of 100 nm in a large field of view (FOV) are first recorded on one end surface of sample and then stitched together to reveal fine pore structure, pore type and pore size distribution. Energy-Dispersive SEM (EDS-SEM) is performed on one the same end of the samples to obtain a mineralogy mapping which will be further used to identify mineralogy. The samples with the diameter of 25.4 mm are scanned by X-ray Micro Computed Tomography (CT) to obtain 3D grayscale images, on which image registration, segmentation and cluster-labelling algorithms are applied to generate multi-mineral digital rock and investigate pore connectivity in 3D. The results of digital rock analysis demonstrate that the pore space of tight sandstone is classified into three types, residual intergranular pore, dissolved pore and micro pore in clay mineral. The results of pore size distribution for each type of pore indicate that the micro pore in clay dominates pore space in tight sandstone. The original intergranular pores are partly filled by clay minerals, where the micro pores contained in form percolation pathway and control the fluid flow through pore pace. The permeability and electrical properties of tight sandstones are dominated by micro pore and have higher dependence of the pore structure than only on porosity. The multi-mineral digital rock proposed in the study can be further applied in numerical simulation of bulk properties and quantitate analysis in nano-geoscience.